Community Service-Based Computer Science Education for Digital Society Development in Shanghai, China - Yadong Shi (Journal of Conflict and Social Class (JCSC), 2025)
The rapid development of digital technology has transformed communication systems, educational practices, and social interaction in modern society. As one of the leading technological and economic centers in Asia, Shanghai, China, has actively implemented digital transformation initiatives that require communities to possess strong digital literacy and technological competence. This community service program aims to strengthen digital society development through computer science education and collaborative community engagement in Shanghai, China. The program employed a qualitative participatory approach involving students, educators, and community members through workshops, mentoring sessions, coding practices, and collaborative digital learning activities. Participants were introduced to computer science concepts, digital communication platforms, computational thinking, and responsible digital participation practices to improve technological understanding and communication competence. The findings demonstrated that participants experienced significant improvement in digital literacy awareness, collaborative communication skills, computational thinking abilities, and confidence in utilizing digital technologies for educational and professional purposes. In addition, collaborative learning environments encouraged active participation, problem-solving competence, and ethical digital behavior among participants. Despite several challenges related to unequal technological access and varying digital competence levels, continuous mentoring and participatory educational approaches contributed positively to the implementation process. Overall, the community service-based computer science education program provided valuable opportunities for improving digital literacy, strengthening community empowerment, and supporting sustainable digital society development in Shanghai. The collaborative educational approaches implemented in this program can also serve as important references for developing digital literacy and community-based technology education programs in other educational and social contexts worldwide.